2020
DOI: 10.1177/1473871619896103
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of three-dimensional pie charts with individually extruded sectors in a geovisualization context

Abstract: This study compares participants’ performance in extracting information from three-dimensional pie charts with individually extruded sectors in a single map frame against two-dimensional pie and bar charts in adjacent map frames. Specifically, we examine the response accuracy and response times of 181 adults who were asked to (1) identify the highest magnitude, (2) estimate a proportion, (3) perform both at the same time, and (4) solve a map-related task using the two chart setups. For each task, charts were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Furthermore, because it has been shown that information processing in "clean" vs cluttered (i.e., simple vs complex) environments may lead to differences in participant performance (e.g., Schnürer et al, 2020), and most, if not all MRT studies have been conducted with a 'clean' background, we generated two unique VEs for the IMRT (Figure 2) to examine the possible effect of background complexity. The first VE surrounds the user with a perceptually limitless, off-white sphere (simple VE)developed with the original paper and pencil version of the MRT in mind.…”
Section: Imrt Developmentmentioning
confidence: 99%
“…Furthermore, because it has been shown that information processing in "clean" vs cluttered (i.e., simple vs complex) environments may lead to differences in participant performance (e.g., Schnürer et al, 2020), and most, if not all MRT studies have been conducted with a 'clean' background, we generated two unique VEs for the IMRT (Figure 2) to examine the possible effect of background complexity. The first VE surrounds the user with a perceptually limitless, off-white sphere (simple VE)developed with the original paper and pencil version of the MRT in mind.…”
Section: Imrt Developmentmentioning
confidence: 99%
“…The results showed that improving visual hierarchy affected viewing behavior and response time. Studies of similar design were conducted with other types of materials, for example 2D and 3D pie charts [12], cartograms [13], maps of spatial accessibility [14], graduated symbols in relation to spatial distance between them [15] or flow maps [16]. All of these provided empirical evidence valuable for formulating the optimal solution for a particular map type, and guidance on how to refine a selected map type.…”
Section: Informationally Equivalent Visualizationsmentioning
confidence: 99%
“…Comparing and evaluating design solutions within thematic map types is a common aim in empirical research in cartography [30][31][32][33]. Yet, heat maps have rarely been used as study material in empirical cartographic user-centered research.…”
Section: Heat Maps and Generalization In Cartographymentioning
confidence: 99%